2012
DOI: 10.1530/eje-11-0725
|View full text |Cite
|
Sign up to set email alerts
|

Associations of IGF1 and its binding proteins with abdominal aortic aneurysm and aortic diameter in older men

Abstract: Objective: Abdominal aortic aneurysm (AAA) is most prevalent in older men. GH secretion declines with age resulting in reduced IGF1 levels. IGF1 and its binding proteins (IGFBPs) are expressed in vasculature, and lower IGF1 levels have been associated with cardiovascular risk factors and disease. However, the relationship of the IGF1 system with aortic dilation and AAA is unclear. We tested the hypothesis that circulating IGF1 and IGFBPs are associated with AAA and aortic diameter in older men. Design: A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Circulating levels of insulin‐like growth factor (IGF) 1 were raised in patients with AAA. Studies examining IGF‐1 levels within the aortic wall itself, however, yielded conflicting results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating levels of insulin‐like growth factor (IGF) 1 were raised in patients with AAA. Studies examining IGF‐1 levels within the aortic wall itself, however, yielded conflicting results.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 106 studies evaluating the levels of proteases, inflammatory markers, acute‐phase reactants and lipids formed the basis for this study ( Fig. ; Table S1, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…The growth factors ferritin, GDF-15, EGF, BMP-4, IGFBP-6, and PDGF-AA have not been studied in AAAs before. Ramos-Mozo et al 38 reported that serum IGFBP-1 in patients with an AAA is significantly higher than in control patients, and Yeap et al 39 determined that IGFBP-1 is independently associated with increased aortic diameter, which makes IGFBP-1 a potential novel AAA biomarker.…”
Section: Growth Factorsmentioning
confidence: 99%
“…TSC1 also has a role in arterial remodeling events by affecting the inflammatory and the growth-promoting response of angiotensin II (43). Insulin-like growth factor 1 (IGF1) expression has been indicated in the vasculature and lower IGF1 expression levels increased the risk of cardiovascular and abdominal aortic aneurysm in a previous study (44). Histological analysis in a swine aneurysm model has demonstrated that IGF1 is upregulated (4-fold) in thrombus organization (45).…”
Section: Discussionmentioning
confidence: 96%